The effect of different attachment systems with implant-retained overdentures on maximum bite force and EMG - ÖZKAN, YASEMİN; ÖZKAN, YAŞAR (WILEY, 2012)
Objective: To compare the effect of different attachment systems with implant-retained overdentures on maximum bite force and muscle activity using electromyography (EMG). Background: Denture retention and stability is of considerable interest in prosthetic dentistry. Materials and methods: Thirty-five patients were examined: 15 edentulous patients treated with mandibular implant-retained overdentures (MIRO) and maxillary dentures (MCD) (two implant-ball attachment) (BC); 10 edentulous patients treated with MIRO and MCD (four implants-bar attachments) (BRC); 10 patients with edentulous mandibular treated with MIRO and maxillary fixed partial dentures (MFPD) (two implant-ball attachments) (BF). Before implant placement all patients received new dentures. After using these dentures for 3 months the maximum bite force and electrical activity of masseter muscle were measured. Two or four implants were then inserted into the intraforaminal region. After osseointegration periods, patients were treated with MIRO which duplicated their dentures and after three months the measurements were repeated. The data were collected and statistically analysed. Results: Muscle activity and chewing ability increased in the second period of measurements. Also chewing time was significantly decreased at the first measurements. The highest muscle activity was observed in the group of patients treated with group BF. Conclusion: The EMG values of the masseter muscle significantly increased when an implant attachments was used in the overdenture.
Keywords: electromyography; implant overdenture; PATIENT SATISFACTION; MASTICATORY FUNCTION; MANDIBULAR OVERDENTURES; SUPPORTED PROSTHESES; MASSETER MUSCLE; DENTURES; BAR